Black rage in New Orleans: police brutality and African American activism from World War II to Hurricane Katrina - Moore, Leonard Nathaniel (Louisiana State University Press, 2010)
Introduction: police violence, New Orleans, and the postwar urban landscape -- Negro police will aid in law and order: the fight for black police in the Crescent City -- Or does it explode?: the black freedom struggle comes to New Orleans -- "We want an end to police brutality": the Black Panthers, desire, and police repression -- The politics of self-defense: Mark Essex, the soul patrol, and black vigilantism -- The right to organize: the Black Organization of Police, mass protest, and the city council hearings -- Black power politics: Ernest "Dutch" Morial and the limits of police reform -- "We are living in a police state": the Algiers tragedy, the maturation of community protest, and the politics of a civilian review board -- Black-on-black crime: the consequences of white flight, the war on drugs, and political indifference -- "A new day in Babylon": the professionalization of the New Orleans Police Department and the claiming of urban public space